APLIKASI PELATIHAN INTERAKTIF PADA PT. KSI (PT. KOSMETIKATAMA SUPER INDAH â INEZ KOSMETIK) - Octorasari, Dian; Dewa, Weda Adistianaya (DINAMIKA DOTCOM, 2016)
Development of the marketing area greatly affect the effectiveness of the work of all departments. One of the problems of efficiency needed by the Training department to reach all areas of marketing PT. KSI. Training by way of face to face directly, to an area that already has branch offices, is a matter that is not very effective in terms of cost and time. Based on these problems, it is very important to establish a media that can simplify the process of training with the concept of Self Learning. Making interactive multimedia learning media using the model of product development-CAI Computer Assisted Instruction, or Computer Assisted Learning-CAL (Computer Assisted Learning), developed by Luther (in Sutopo, 2003: 32). According Sutopo who found Multimedia development methodology consists of six stages, namely the concept, design, collecting materials, assembly, testing and distribution. The stages are very complete in making computer-based instructional media. Furthermore, the authors apply the Hierarchical Navigation method as implemented into the design of Interactive Training Applications at PT. KSI. From the results, the researchers made a model of training using computer-based interactive multimedia. This training model can improve the cost effectiveness and time for employee training. With the design and implementation of interactive training applications, it can be a good contribution to the PT. KSI. Especially in terms of cost and time efficiency.Key Words:Training Applications, interactive multimedia